Seismic Shifts in Responsibility: Preserving and Advocating for Trans-Inclusive Experiences within Education Systems - Álvaro Gamio Cuervo (Gender a Výzkum)
Review of book Bartholomaeus, C., Riggs, D. W. Transgender People and Education